Established and emerging techniques for the study of microglia: visualization, depletion, and fate mapping - Bobotis, Bianca Caroline; Halvorson, Torin; Carrier, Micaël; Tremblay, Marie-Ève (Frontiers in Cellular Neuroscience, 2024)
The central nervous system (CNS) is an essential hub for neuronal communication. As a major component of the CNS, glial cells are vital in the maintenance and regulation of neuronal network dynamics. Research on microglia, the resident innate immune cells of the CNS, has advanced considerably in recent years, and our understanding of their diverse functions continues to grow. Microglia play critical roles in the formation and regulation of neuronal synapses, myelination, responses to injury, neurogenesis, inflammation, and many other physiological processes. In parallel with advances in microglial biology, cutting-edge techniques for the characterization of microglial properties have emerged with increasing depth and precision. Labeling tools and reporter models are important for the study of microglial morphology, ultrastructure, and dynamics, but also for microglial isolation, which is required to glean key phenotypic information through single-cell transcriptomics and other emerging approaches. Strategies for selective microglial depletion and modulation can provide novel insights into microglia-targeted treatment strategies in models of neuropsychiatric and neurodegenerative conditions, cancer, and autoimmunity. Finally, fate mapping has emerged as an important tool to answer fundamental questions about microglial biology, including their origin, migration, and proliferation throughout the lifetime of an organism. This review aims to provide a comprehensive discussion of these emerging techniques, with applications to the study of microglia in development, homeostasis, and CNS pathologies.